Toxicity Test of Some Selected Wild Mushrooms of Nepal - Ghimire, Madhu Bilash; Aryal, Hari Prasad; Lakhey, Pramesh Bahadur; Ranjitkar, Rajeshwor; Bhatta, Yagya Raj (Journal of Plant Resources, 2022)
People have been using wild mushrooms in their diet and also as sources of income, but most of them do not have the proper knowledge to distinguish edible mushrooms from poisonous ones. The main objective of this research is to determine and document toxicity of some selected wild mushrooms of Nepal. Samples were collected based on their use practices by the local communities, representing different ecological belts. The tests were carried out following the protocol described in ‘Test Guideline no. 425: Acute Oral Toxicity: Up-and-Down Procedure’. Mice (Mus musculus) were administered with aqueous solution of each sample in a single dose by gavage using a stomach tube on the basis of their body weight and were observed for the signs of toxicity. The tested samples of Boletellus emodensis, Caloboletus calopus, Daedalea quercina, Lactifluus volemus, Lyophyllum decastes, Macrolepiota albuminosa, Phellodon niger, Phylloporus bellus, Russula delica, R. emetica, R. senecis, Strobilomyces strobilaceus, Termitomyces eurrhizus, T. le-testui, T. mammiformis, T. robustus, T. striatus f. brunneus, T. straitus f. pileatus, Trametes vernicipes and Trichaptum biforme revealed LD50 value > 2000 mg.kg-1 body weight indicating that they may be harmful if swallowed . However, in case of Hapalopilus rutilans, LD50 value of 1212 mg.kg-1 body weight was observed confirming that it is harmful when swallowed.